Description of a new Synergus species from China and comments on other inquiline species (Hymenoptera: Cynipidae: Synergini) - Pujade-Villar, Juli; Wang, Yiping; Chen, Tianlin; Shen, Jie; Ferrer-Suay, Mar (Zootaxa, 2017)
A new species, Synergus mongolicus Pujade-Villar & Wang n. sp., is described from galls collected on twigs of Quercus mongolica. The morphological characters useful for differentiating the new species are also discussed. Three inquilines species are recorded from China for the first time: Saphonecrus shirakashii, Synergus belizinellus and S. symbioticus. Saphonecrus tianmushanus is considered a n. syn. of S. shirakashii based on comparison of the types. Saphonecrus taiwanensis Pujade-Villar new name is proposed for Saphonecrus lithocarpii Schwéger & Melika, 2015 by homonymy with S. lithocarpi Pujade-Villar, Guo, Wang & Chen, 2015 and finally Saphonecrus chinensis Tang & Schwéger, 2015 is considered a n. syn. of S. lithocarpi Pujade-Villar, Guo, Wang & Chen, 2015.